Statyka Przestrzennej Konstrukcji Prętowej Płyty Strukturalnej - Peła, R. (Engineering Transactions, 1971)
Here presented are problems connected with the application of a continuous model for statics calculations of "dense" rod covers, called structural plates. This is understood to be a certain kind of spatial grid whose every nodes, connected with a system of rods, are situated on two planes spaced at no excessive distance from each other. The two-dimensional model of a "fibrous medium" is applied to describe the state of stress and displacement of the structural plate.